Arranjos produtivos: análise da experiência do setor oleiro cerâmico de Iranduba (AM) - Monteiro, Adriano Santos (2008)
In face of the emergence of a Local Productive Arrangement - LP A to replace the current industrial agglomeration known as Cluster in the municipality of lranduba and its surroundings, the study characterizes the production process and administrative area included in the industries. The aim therefore is to identify the necessary points of transformation accompanied by benefits that change can bring to the whole society that depends on the pottery industry to survive. Although cooperation between companies occur potters of Iranduba the results of the study show that there is an outbreak of local productive arrangement, only interaction between a cluster of companies in terms of needs focus. In this scope, it is pointed out as main results which find of an archaic system of production based on family structure and lack of direction of public policies that encourage the development of LPA.